2017
DOI: 10.1007/s40261-017-0565-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ombitasvir/Paritaprevir/Ritonavir and Dasabuvir with or without Ribavirin for Treatment of Hepatitis C Virus Genotype 1: A Systematic Review and Meta-analysis

Abstract: The current meta-analysis showed a high efficacy for the OBV/PTV/r regimen in the treatment of HCV genotype 1 (with DSV) infection, regardless of the presence of cirrhosis or former treatment failure. Adding RBV to this regimen slightly decreased the relapse rate. Future studies with larger sample sizes are required to investigate the efficacy of this regimen in other HCV genotypes and to establish the evidence about the effect of adding RBV to OBV/PTV/r + DSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
2
13
1
1
Order By: Relevance
“…With respect to patients on PTV/OBV/r therapy, a stratified analysis of a Japanese clinical study reported that the SVR rate (90.5%) in patients with cirrhosis was lower (96.0%) than in patients without cirrhosis . However, two meta‐analyses found no difference in the SVR rate between patients with and without cirrhosis . In the present study, the SVR rate of patients with cirrhosis on PTV/OBV/r therapy was significantly lower than that of patients without cirrhosis, irrespective of previous DAA‐based treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…With respect to patients on PTV/OBV/r therapy, a stratified analysis of a Japanese clinical study reported that the SVR rate (90.5%) in patients with cirrhosis was lower (96.0%) than in patients without cirrhosis . However, two meta‐analyses found no difference in the SVR rate between patients with and without cirrhosis . In the present study, the SVR rate of patients with cirrhosis on PTV/OBV/r therapy was significantly lower than that of patients without cirrhosis, irrespective of previous DAA‐based treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…The tolerability profile of IFN-free regimens in the current analysis was in accordance with clinical trials and realworld studies (40)(41)(42)(43)(44)(45). A total of 41% of the entire cohort reported at least one AE, more often in RBV-containing group.…”
Section: Discussionsupporting
confidence: 78%
“…It is not intended as a direct comparison between individual drugs, but to describe the patients treated and measure the extent to which the recommendations in the introduction protocol were implemented. Cure rates, based on data from 85% of the cohort, were generally as high as expected from either RCTs [17] or recent observational studies [1823], with some variation between genotypes. Most of the patients were treated with the recommended combinations of the drugs under study, and the initially moderate adherence to the drug recommendations increased over time, with the increasing inclusion of drugs and drug combinations in the introduction protocol.…”
Section: Discussionmentioning
confidence: 53%